MODEL PEMASARAN IKAN CAKALANG (KATSUWONUS PELAMIS) DI KOTA KUPANG - Naharuddin Sri (Partner, 2013)
Marketing Model of Skipjack Tuna in Kupang Regency.  The study was aimed to identify marketing model of Skipjack Tuna (Katsuwonus pelamis) in Kupang City especially in Namosain, Oeba and Oesapa markets. The samples were selected by using Cluster Random Sampling method.  Descriptive analysis was used to analyse model ofevery marketing channel of Skipjack Tuna.  The study disclosed that there were 5 channels in Skipjack Tuna marketing and 2 marketing models. The first model, the fishermen made partnership relation with owner of Skipjack Tuna fishing boat as well as the owner of  equipment and trader.  The second model, the fishermen had no partership. Condusive marketing model for fisherman is still need with support from govermant and other institute. Keyword: Skipjack Tuna, Marketing Model, Marketing Channel